A Combined Inhibiting Effect of Sodium Alginate and Sodium Phosphate on the Corrosion of Magnesium Alloy AZ31 in NaCl Solution. Issue 8 (4th June 2016) - Hou, Lifeng; Dang, Ning; Yang, Haiyan; Liu, Baosheng; Li, Yonggang; Wei, Yinghui; Chen, Xiao-Bo
Abstract : The inhibiting effect of joint-addition of sodium alginate (SA) and sodium phosphate (SP) on corrosion of magnesium (Mg) alloy AZ31 (3 wt% aluminum and 1 wt% zinc) in 3.5 wt% NaCl solution was investigated by electrochemical impedance spectroscopy, potentiodynamic polarization analysis, mass loss measurements, and scanning electron microscopy (SEM) equipped with energy dispersive X-ray spectroscopy (EDS). Results reveal a combined inhibiting effect derived from the presence of SA and SP with respect to Mg alloy AZ31 and an optimal inhibition efficiency in terms of corrosion of AZ31 substrate was yielded in 3.5 wt% NaCl electrolyte containing 0.05 wt% SA and 0.15 wt% SP. SEM-EDS examination suggested that such a promising combined inhibiting mechanism could be attributed to the formation of a compact, homogeneous and protective composite film. Chemical composition study through Fourier transform infrared spectroscopy elucidates that such a protective film contains not only conventional magnesium hydroxide as a result of corrosion of Mg alloy AZ31, but SA and SP through chemical adsorption on the surface of Mg alloy AZ31.